Pengaruh Reputasi Dalam Membangun Kepercayaan Masyarakat Terhadap Rumah Sakit Umum Pringsewu - Rafiq, Muhammad; Kurniawan, Bayu Tri (Jurnal Manajemen dan Keuangan, 2009)
The purpose of this research is to test the reputation variable wich influenced public trust of hospital. In this research use association model and correlates reputation to public trust and then regressed that variables to prove the hypotesis. This research, a 100 respondent has taking for the samples. The sampling method uses purposive sampling technique.The result, that hypotesis be proved that reputation influenced trust (sig 0,000 < 0,05), R= 0,567 and R square 32,2%. So the reputation is one of many factors influenced toward public hospital.Keywords: Reputation, trust, hospital